Unintentional Impact of EU Directives on the Cultural Heritage - Ivanc, Tjaša (LeXonomica, 2011)
The paper deals with the position of cultural heritage and the problems of fixing the boundaries between the national cultural sector and the EU jurisdiction in this area. Policies of cultural heritage protection regime are not part of the Treaty on the Functioning of the EU. Nevertheless, the action of the EU is aimed at co-financing and supporting of its conservation and safeguarding. Therefore, several EU Directives, which regulate other areas (environmental protection, construction of new buildings) and are incorporated into national legislation, could be problematic because of their detrimental effect on the sustainable conservation of the European cultural heritage. The authoress puts forward proposals for potential impact and involvement of the competent national authorities in the legislative process of adopting EU legislation in other areas, which could detrimentally affect the individual protection of cultural heritage.Nenamerni vpliv direktiv EU na kulturno dediščino. Prispevek obravnava položaj kulturne dediščine in probleme razmejitve med nacionalnim kulturnim sektorjem in pristojnostmi EU na tem področju. Politika varovanja kulturne dediščine ni del ureditve Pogodbe o delovanju EU, temveč EU skrbi za sofinanciranje in podporo obnavljanju in ohranjanju kulturne dediščine. Zato so na tem področju lahko problematične številne direktive EU na drugih področjih zakonodajnega urejanja EU (npr. varstvo okolja, graditev novih objektov), ki so z implementacijo vključene v nacionalne zakonodaje in ki v večji ali manjši meri škodljivo vplivajo na trajnostno ohranjanje evropske kulturne dediščine. Avtorica v prispevku poda predloge za možen vpliv in vključitev pristojnih nacionalnih organov v zakonodajni postopek sprejemanja aktov EU na drugih področjih, ki lahko škodljivo vplivajo na konkretno varstvo kulturne dediščine.
Keywords: cultural heritage; EU directives; detrimental effect; legislative procedure of the EU; economic value of cultural heritage